2011
DOI: 10.1016/j.breast.2011.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between mastalgia and fibromyalgia? Comparing prevalence and symptom severity

Abstract: To determine the prevalence of mastalgia in patients with fibromyalgia (FM) and the prevalence of FM in patients with mastalgia in order to investigate coexistence, and to compare the pain patterns in the case of mastalgia or FM alone versus the two in combination. Fifty consecutive patients with mastalgia and 50 consecutive patients with FM were assessed and examined both for the existence and severity of mastalgia and FM. A high proportion of patients with mastalgia (36%) fulfilled the criteria for FM and 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 23 publications
2
17
0
3
Order By: Relevance
“…However, even though many women with Dercum’s disease have painful lipomas in the breast, both idiopathic mastalgia and lipomas are common in the breast and it is undecided if a single painful lipoma of the breast should render the diagnosis Dercum’s disease. On the other hand, it has been discussed if chronic pain syndromes, such as fibromyalgia, might be associated with mastalgia [35]. …”
Section: Definition and Clinical Descriptionmentioning
confidence: 99%
“…However, even though many women with Dercum’s disease have painful lipomas in the breast, both idiopathic mastalgia and lipomas are common in the breast and it is undecided if a single painful lipoma of the breast should render the diagnosis Dercum’s disease. On the other hand, it has been discussed if chronic pain syndromes, such as fibromyalgia, might be associated with mastalgia [35]. …”
Section: Definition and Clinical Descriptionmentioning
confidence: 99%
“…The use of EMG to obtain information about muscle response or electrical activity to a nerve's stimulation of a muscle provides information to the clinician regarding many conditions such as muscle aches, muscle weakness, anomalies related to muscle movements, and muscle atrophy (24,29). Although many studies have evaluated the relationship between fibromyalgia and the nociceptive flexion reflex, we did not find any study evaluating the relationship of nociceptive flexion reflex with mastalgia (30,31). Furthermore, only a few studies have evaluated the relationship between fibromyalgia and CSP, and we found no study investigating the relationship between mastalgia and CSP (25)(26)(27).…”
Section: Discussionmentioning
confidence: 83%
“…For example, both are more prevalent in the female population, both are believed to develop due to stress, and both include clinical similarities (30,32). In their study including 50 patients with mastalgia and 50 with fibromyalgia, Genc et al (31) reported that 36% of mastalgia patients met fibromyalgia criteria, and 42% of fibromyalgia patients had mastalgia complaints. In another study by Sen et al (30), 47.2% of 53 patients with fibromyalgia had mastalgia and 37.7% of 61 patients with mastalgia met the diagnostic criteria for fibromyalgia syndrome (30).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, one of the main outcomes of their study was the finding of a possible association between a common form of mastalgia and unexplained pain syndromes. The second study to demonstrate a link between mastalgia and FMS was reported by Genc et al in 2011 21 . In that study, the BPQ was used as a relatively objective assessment tool for evaluating mastalgia.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, 13 out of 61 mastalgia patients in our study had been previously treated for a psychiatric disorder. To the best of our knowledge, only two clinical studies on the relationship between mastalgia and FMS have been reported to date 1 , 21 . One is the 2006 study by Johnson et al, which demonstrated the association between mastalgia and various chronic pain disorders, including irritable bowel syndrome, chronic pelvic pain and FMS 1 .…”
Section: Discussionmentioning
confidence: 99%